Heterogenous within-herd seroprevalence against epizootic hemorrhagic disease virus type 8 (EHDV-8) after massive virus circulation in cattle in France, 2023 - Corinne Anthonioz; Yann Abadie; Elodie Reversat; Annie Lafargue; Manon Delalande; Thierry Renaudineau; Laurent Delobel; Nathalie Verdeille; David Ngwa-Mbot; Kristel Gache; Emmanuel Garin; Fabien Corbiere (Frontiers in Veterinary Science)
Background and objectivesThe emergence of Epizootic Hemorrhagic Disease Virus-8 (EHDV-8) in mainland France in 2023 led to thousands of clinical outbreaks in cattle herds and likely led to the natural immunization of a large number of animals. However, uncertainties persist regarding the extent of this immunity, both within herds and across affected regions. This study therefore aimed at investigating the variability of within-herd seroprevalence in clinically affected and non-affected herds across geographical areas with differing levels of disease incidence.MethodologyA study was launched in February 2024 to assess the variability of within-herd seroprevalence in three geographical areas with varying EHDV-8 clinical incidence. A total of 2,763 serums samples from cattle over 24 months in 30 herds with clinical outbreaks and 31 herds without reported clinical case were analyzed using a commercial competitive ELISA.ResultsA strong south–north seroprevalence gradient was observed, with the highest animal-level seroprevalence evidenced in the southernmost zone (Pyrenean Piémont) (82.6%, CI 95%: 81.1–83.9), which also experienced the highest incidence of clinical outbreaks. In contrast, significantly lower seroprevalence levels were found in the more northern areas: (zone 2: 11.6, 95% CI: 10.7–12.7; zone 3: 0.3, 95% CI: 0.1–1.1), where clinical outbreaks were less frequent. The within-herd seroprevalence varied widely among herds but was significantly higher in those located in the southernmost zone, compared to other areas. Within each zone, no significant differences in seroprevalence were observed between clinical outbreak herds and non-outbreak herds.DiscussionThis study highlights significant geographic and between herd variability in seroprevalence against EHDV-8 after the major virus circulation experienced in 2023, and provides critical insights into regional risks and the potential impact of future EHDV-8 circulation.